2014
DOI: 10.1302/0301-620x.96b3.32702
|View full text |Cite
|
Sign up to set email alerts
|

Short-stem uncemented primary reverse shoulder arthroplasty

Abstract: Short uncemented humeral stems can preserve humeral bone stock and facilitate revision surgery but may be prone to malalignment or loosening, especially when used in reverse total shoulder replacement (TSR). We undertook a retrospective review of 44 patients with a mean age of 76 years (59 to 92) who underwent primary reverse TSR with a short uncemented humeral stem. There were 29 females. The indications for joint replacement included cuff tear associated arthropathy (33), avascular necrosis (six), post-traum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
58
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(63 citation statements)
references
References 23 publications
5
58
0
Order By: Relevance
“…Although a number of studies have evaluated the radiographic changes observed with these implants, most analyzed results with anatomic shoulder replacement. 14,18,24,28,29,38,45,48,51,52,54 Early …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Although a number of studies have evaluated the radiographic changes observed with these implants, most analyzed results with anatomic shoulder replacement. 14,18,24,28,29,38,45,48,51,52,54 Early …”
Section: Discussionmentioning
confidence: 99%
“…23,24,39,43 Recently, however, the use of press-fit humeral components has become more prevalent. 12,14,18,28,38,45,54 Proposed advantages of press-fit fixation include decreased operative time and lower complication rates with stem removal during revision surgery. Early-generation press-fit humeral components were associated with high loosening rates and poor results.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…8 Among RTSA, the glenoid component has a relatively low rate of loosening. 5 The effect of wear debris in the RTSA may instead be associated with a higher rate of loosening of the humeral stem. 3 Since approval by the United States Food and Drug Administration in 2004, RTSA prostheses are increasingly used for glenohumeral arthropathy associated with a deficiency of the rotator cuff.…”
mentioning
confidence: 99%
“…Giuseffi et al also reported on 44 reverse total shoulders performed using the Comprehensive Mini stem (Biomet, Warsaw, IN) with at least 24-months follow-up [35]. Unfortunately, a functional outcome score was not reported but 97% had no pain or only mild pain.…”
Section: Biometmentioning
confidence: 99%